2008
DOI: 10.1007/s11250-008-9199-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary alternative lipid sources on haematological parameters and serum constituents of Heterobranchus longifilis fingerlings

Abstract: The worldwide increase in aquaculture production and the decrease of wild fish stocks has made the replacement of fish oil (FO) in aquafeed industry a priority. Therefore, the use of terrestrial animal fats and vegetable oils, which has lower cost and larger supplies, may be good as substitute for FO. This study investigate the effects of total replacement of FO by two terrestrial animal fats (pork lard and poultry fat) and three vegetable oils (palm kernel oil, sheabutter oil and sunflower oil) on haematologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
3
23
1
Order By: Relevance
“…Nevertheless, an increase in the levels of plasma and serum transaminases has been associated with liver damage in marine (Lemaire et al, 1991) and freshwater species (Babalola et al, 2009), which was directly related to histopathological findings. In the present study, the normal morphology of livers of fish fed the different diets might indicate that differences in ALT and AST found among diets were possibly not relevant.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, an increase in the levels of plasma and serum transaminases has been associated with liver damage in marine (Lemaire et al, 1991) and freshwater species (Babalola et al, 2009), which was directly related to histopathological findings. In the present study, the normal morphology of livers of fish fed the different diets might indicate that differences in ALT and AST found among diets were possibly not relevant.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, Babalola et al. () found that vegetable oils (sunflower and cacao) increase hepatic enzyme activity in channel catfish. In general, different studies about fish nutrition on different species reported similar results on haematological and biochemical parameters when FO replaced with VO in diets.…”
Section: Discussionmentioning
confidence: 99%
“…Positive relationship between RBC in Paralichthys dentatus and dietary protein level was observed by Daniels and Gallagher (2000). According to Babalola et al (2009), erythrocyte count in Heterobranchus longifilis was significantly affected by a dietary lipid source (higher in fish fed with sunflower and poultry lipids compared to those fed with other vegetable or animal fat). A significant effect of the lipid source on erythrocyte count was confirmed by Demska-Zakęś et al (2012) for Tinca tinca.…”
Section: Erythrocytesmentioning
confidence: 95%